If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(a + -4) + -2a = 19 + 3(a + 3) Reorder the terms: 7(-4 + a) + -2a = 19 + 3(a + 3) (-4 * 7 + a * 7) + -2a = 19 + 3(a + 3) (-28 + 7a) + -2a = 19 + 3(a + 3) Combine like terms: 7a + -2a = 5a -28 + 5a = 19 + 3(a + 3) Reorder the terms: -28 + 5a = 19 + 3(3 + a) -28 + 5a = 19 + (3 * 3 + a * 3) -28 + 5a = 19 + (9 + 3a) Combine like terms: 19 + 9 = 28 -28 + 5a = 28 + 3a Solving -28 + 5a = 28 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -28 + 5a + -3a = 28 + 3a + -3a Combine like terms: 5a + -3a = 2a -28 + 2a = 28 + 3a + -3a Combine like terms: 3a + -3a = 0 -28 + 2a = 28 + 0 -28 + 2a = 28 Add '28' to each side of the equation. -28 + 28 + 2a = 28 + 28 Combine like terms: -28 + 28 = 0 0 + 2a = 28 + 28 2a = 28 + 28 Combine like terms: 28 + 28 = 56 2a = 56 Divide each side by '2'. a = 28 Simplifying a = 28
| 0.04y+0.12(200-y)=0.34y | | 0.2(x+1)=10 | | 5x^2+1=0 | | 0.09y+0.09(900-y)=0.50y | | 1.2x-3.3=0.6x-2.58 | | 6x-16=2x+16 | | 5-8n+3n=10-85 | | 5+6=-2-15 | | -3x+1=x+1 | | 9*(-5)= | | 215-33x=33x+15 | | 2(67-3y)=2(67-3y) | | 3(3x+3)-6=3x-3 | | 14-7x=96-21x | | y=x^2+12x-9 | | 12-2a+a+3=0 | | 14x^2+28x+14=0 | | -7x+6+5x=-3x+11 | | 6x^2+15x+27=0 | | 3x-6+6(x+1)=7x+2 | | 10x^2+16x+24=0 | | x+12=2x+5 | | -3x^3-6x=0 | | 2-7(y+2)=9-3y | | -7[5+3(6+9)]= | | (6y^3-y^2+4)(4y^2+y+1)= | | -7x+7+5x=-3x+12 | | 8.5p=7.5p | | -7x+4+5x=-3x+9 | | 0.2(x+1)=0.3(x+11) | | -6(x+1)+2(7x+9)= | | 2x+149=9x-5 |